2004
DOI: 10.1081/ias-120027229
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Anti‐recombinant Human Erythropoietin (rhEPO) Monoclonal Antibody

Abstract: Anti-rhEPO McAb is valuable for the determination of recombinant human erythropoietin (rhEPO) levels for diagnosis of renal anemia and for doping control analysis. In this paper, anti-rhEPO hybridoma was prepared by fusion of SP2/0 murine myeloma cells with spleen cells isolated from immunized BALB/c mouse, using an enzyme-linked immunosorbent assay (ELISA) method to screen the positive hybridoma. The purified McAb was characterized by ELISA, SDS-PAGE, and Western-blotting. Experimental results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The SMX-MAb was fully characterized and the results showed that the SMX-MAb was of the subclass IgG 1 and the affinity constant of the SMX-MAb with SMX-HSA was 2.3 )/10 8 l/mol. The affinity constant of MAb normally ranges from 10 5 Á/10 9 L/mol (Yan et al 2004). The results proved that the immunogenicity of SMX-HSA was so high that it induced high immuno-response to produce high affinity antibody.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The SMX-MAb was fully characterized and the results showed that the SMX-MAb was of the subclass IgG 1 and the affinity constant of the SMX-MAb with SMX-HSA was 2.3 )/10 8 l/mol. The affinity constant of MAb normally ranges from 10 5 Á/10 9 L/mol (Yan et al 2004). The results proved that the immunogenicity of SMX-HSA was so high that it induced high immuno-response to produce high affinity antibody.…”
Section: Discussionmentioning
confidence: 79%
“…The antibody's specificity determines the specificity and sensitivity of the immunoassay. The K aff value represents the combined stability of Ag Á/ Ab, which is a crucial parameter that can reflect the quality of the Ab (Yan et al 2004). In order to produce highly specific antibodies to SMX and to select better hybridoma cells to generate monoclonal antibodies only recognizing SMX, SMX was bound to HSA to form an antigen for animal immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only indirect competition-enzyme linked immunosorbent assay can provide the real thermodynamic affinity of the antibody for its antigen. They can be applied to a varity of experimental situations, some of which are reviewed in Goldberg et al [13,27]. The method used here is adapted from friguet.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion procedure and positive clone screening method were the same as reported previously. (9) Six cell clones that produced antibody against GP-1D8 were selected and expanded, followed by single-cell cloning for three times using a limiting dilution method. (9) One clone of the hybridoma-secreting antibody against GP-1D8 was characterized.…”
Section: Methodsmentioning
confidence: 99%